Trends in international migration and remittance flows: Case of Bangladesh (Journal of the Bangladesh Agricultural University, 2010)
International migration from Bangladesh has become a defining characteristic of the country. Especially since 1980s, large scale labour migration has become a common phenomenon of Bangladesh. This paper examines the various issues of international migration and remittance flows of Bangladesh on the basis of the secondary data generated from various reports of government and non-government organizations and of various publications of home and abroad. With a few exceptions, manpower export has been showing increasing trend year by year. Most of the expatriates, who are largely unskilled, are working in the Middle East countries and in the UK and the USA. Like overseas employment, remittances flow has been increasing every year with its increased share in GDP and export earnings. Major share of total remittances come from the Middle East countries. But individually the position of the USA is just behind Saudi Arabia over the last few years. Finally it can be concluded that proper attention should be given on overseas migration in order to keep the unemployment rate within tolerable level and to increase the amount of remittances which is an important source of foreign exchange. Keywords: International migration; Remittance; Expatriate; Employment; Increased share in GDP DOI: 10.3329/jbau.v7i2.4751 J. Bangladesh Agril. Univ. 7(2): 387-394, 2009